SURGICAL TREATMENT OF DRUG-RESISTANT EPILEPSY (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Epilepsy is one of the most common chronic neurological diseases: according to WHO, about 50 million people worldwide currently suffer from active epilepsy with ongoing epileptic seizures or the need to take antiepileptic drugs (AEDs), and about 5 million new cases of this disease are diagnosed annually. According to the results of a large-scale study conducted in 14 regions of the Russian Federation, the age-standardized prevalence of epilepsy was 3.4 people per 1000 population. This article will describe a specific clinical case of a patient suffering from drug-resistant epilepsy, examination of his brain and the nature of the surgical operation performed by the Department of Neurosurgery at Samara State Medical University.